Ecosytem Services: A Rapid Assessment Method Tested at 35 Sites of the LTER-Europe Network - Dick, Jan; Al-Assaf, Amani; Andrews, Chris; Díaz-Delgado, Ricardo; Groner, Elli; Halada, Ľuboš; Izakovičová, Zita; Kertész, Miklós; Khoury, Fares; Krasić, Dušanka; Krauze, Kinga; Matteucci, Giorgio; et al. (Ekológia Bratislava, 2014)
The identification of parameters to monitor the ecosystem services delivered at a site is fundamental to the concept’s adoption as a useful policy instrument at local, national and international scales. In this paper we (i) describe the process of developing a rapid comprehensive ecosystem service assessment methodology and (ii) test the applicability of the protocol at 35 long-term research (LTER) sites across 14 countries in the LTER-Europe network (www.lter-europe.net) including marine, urban, agricultural, forest, desert and conservation sites. An assessment of probability of occurrence with estimated confidence score using 83 ecosystem service parameters was tested. The parameters were either specific services like food production or proxies such as human activities which were considered surrogates for cultural diversity and economic activity. This initial test of the ecosystem service parameter list revealed that the parameters tested were relatively easy to score by site managers with a high level of certainty (92% scored as either occurring or not occurring at the site with certainty of over 90%). Based on this assessment, we concluded that (i) this approach to operationalise the concept of ecosystem services is practical and applicable by many sectors of civil society as a first screen of the ecosystem services present at a site, (ii) this study has direct relevance to land management and policy decision makers as a transparent vehicle to focus testing scenarios and target data gathering, but (iii) further work beyond the scale investigated here is required to ensure global applicability.